Combined Radio- and Chemotherapy for Non-Small Cell Lung Cancer: Systematic Review of Landmark Studies Based on Acquired Citations - Nieder, Carsten; Pawinski, Adam; Andratschke, Nicolaus H. (Frontiers in Oncology, 2013)
The important role of combined chemoradiation for several groups of patients with non-small cell lung cancer (NSCLC) is reflected by the large number of scientific articles published during the last 30 years. Different measures of impact and clinical relevance of published research are available, each with its own pros and cons. For this review, article citation rate was chosen. Highly cited articles were identified through systematic search of the citation database Scopus. Among the 100 most often cited articles, meta-analyses (n=5) achieved a median of 203 citations, guidelines (n=7) 97, phase III trials (n=29) 168, phase II trials (n=21) 135, phase I trials (n=7) 88, and others combined 115.5 (p=0.001). Numerous national and international cooperative groups and several single institutions were actively involved in performing often cited, high-impact trials, reflecting the fact that NSCLC is a world-wide challenge that requires research collaboration. Platinum-containing combinations have evolved into a standard of care, typically administered concurrently. The issue of radiotherapy fractionation and total dose has also been studied extensively, yet with less conclusive results. Differences in target volume definition have been addressed. However, it was not possible to test all theoretically possible combinations of radiotherapy regimens, drugs and drug doses (lower radiosensitizing doses compared to higher systemically active doses). That is why current guidelines offer physicians a choice of different, presumably equivalent treatment alternatives. This review identifies open questions and strategies for further research.